The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4025/actascianimsci.v41i1.42808
|View full text |Cite
|
Sign up to set email alerts
|

Leaf area estimate of <i>Pennisetum glaucum<i> by linear dimensions

Abstract: Leaf area measurements are of the main parameters used in agronomic studies to evaluate plant growth. The current study used a non-destructive method based on linear leaf dimensions (length and width) to select the regression model to estimate millet (Pennisetum glaucum) leaf area. For two millet genotype (IPA BULK 1 BF and ADR 300) 128 randomly-chosen leaves were measured at different vegetative growth stages. Measures of length and width of each leaf were made using digital calipers. Leaf area was measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 17 publications
1
20
0
6
Order By: Relevance
“…The best fit model was used to predict the weight of the cladodes as a function of thickness (T) and product between L and W (LW), and regression studies were performed using linear, gamma and power models ( Table 1). The linear and power models with normal distributions assumed that the response of the dependent variable was in the range of -∞ to ∞, and the gamma models with gamma distributions assumed that the response of the dependent variable was in the range of 0 to ∞ (Lucena et al, 2018b;Leite et al, 2017;Leite et al, 2019), (Table 1). Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The best fit model was used to predict the weight of the cladodes as a function of thickness (T) and product between L and W (LW), and regression studies were performed using linear, gamma and power models ( Table 1). The linear and power models with normal distributions assumed that the response of the dependent variable was in the range of -∞ to ∞, and the gamma models with gamma distributions assumed that the response of the dependent variable was in the range of 0 to ∞ (Lucena et al, 2018b;Leite et al, 2017;Leite et al, 2019), (Table 1). Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Corroborating this assertion, several authors have tested and adjusted these models for other species, such as Crotalaria juncea [8], Litchi chinensis Sonn. [9], Artocarpus heterophyllus [10], Cucurbita moschata [11], Pennisetumglaucum [12] and Plectranthus barbatus Andrews [13]. Table 3 describes the nine models of equations generated for the estimation of the leaf area of Acacia mangium Willd.…”
Section: Ssionmentioning
confidence: 99%
“…Based on the leaf dimensions of several species and without the destruction of the sample, several studies have reported the use of mathematical models to estimate leaf area [8,9,10,11,12,13,14]. With respect to A. mangium Willd., A non-destructive methodology for the determination of its leaf area is of great importance, since there are no mathematical equations in the literature that allow this measurement in the specie.…”
Section: Introductionmentioning
confidence: 99%
“…Para determinação da área de cladódio são utilizados métodos indiretos e não destrutivos, permitindo avaliações sucessivas do mesmo cladódio (Lucena et al, 2019). O desenvolvimento de modelos de regressão a partir das medidas lineares de folhas para determinar a área foliar tem sido muito útil no estudo do crescimento e desenvolvimento das plantas (Achten et al, 2010).…”
Section: Introductionunclassified
“…O desenvolvimento de modelos de regressão a partir das medidas lineares de folhas para determinar a área foliar tem sido muito útil no estudo do crescimento e desenvolvimento das plantas (Achten et al, 2010). Os modelos matemáticos são vantajosos porque são rápidos, não destroem as plantas e são fáceis de manusear em condições de campo (Leite, Lucena, Cruz, Sá Júnior, & Simões, 2019). Diversos estudos utilizando dimensões lineares na estimativa da área de cladódio foram estabelecidos para várias espécies de cactáceas [Opuntia ficus-indica (Reis, Gazarini, Fonseca, & Ribeiro, 2016), O. stricta (Lucena, Leite, Simões, Simões, & Almeida, 2018), Nopalea cochenillifera (Lucena et al, 2019)], e geraram equações com alta precisão.…”
Section: Introductionunclassified